Al-Zamakhsari and the Miraculous Nature of Al-Qur'an - M. Amin Nurdin (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
Al-Zamakhsari’s description of the Qur’anic exegesis is not only revealing the meaning contained in Al-Qur’an, but also, he disclosed the secrets of the i’jaz of al-Qur’an. The method used by al-Zamakhsari in explaining this by practicing theories given by the earlier ulemas which condensed in the method of nazm. With nazm, word, meaning and axioms of the grammatical rules orderly organized which then manifest themselves in ultimate non-imitative beauty of eloquence, highest composition, perfect style and depth of meanings.